The Role of Internet to Bridge Language Gaps in Learning English as a Foreign Language in Solo's Multilingual - Astrini, Atik; Yeni Prastiwi; Hapy Adityarini (PT. Banjarese Pacific Indonesia, 2024)
This study investigates the role of the internet in bridging language gaps and enhancing English as a Foreign Language (EFL) instruction within Solo's multilingual context. The focus is on how internet resources aid students in navigating between Bahasa Jawa, Bahasa Indonesia, and English, reflecting the multilingual dynamics of EFL classrooms. Utilizing a qualitative approach, semi-structured interviews were conducted with students from grade XII public senior high schools in Solo, Central Java. The findings reveal that the internet plays a significant role in facilitating language learning by providing access to diverse resources and interactive platforms. It is reported that internet tools help them create more engaging and culturally relevant lessons, which cater to the multilingual backgrounds of the students. Students highlighted that online resources offer immediate feedback, diverse learning materials, and opportunities for practicing English in real-world contexts, which are crucial for mastering a foreign language. Moreover, the study shows that the internet supports students in developing digital literacy skills, which are essential for effective language learning in the 21st century. The use of internet-based learning tools helps students seamlessly transition between languages, enhancing their overall language proficiency and confidence in using English. This research underscores the importance of integrating internet resources in EFL education to address the unique linguistic needs of students in multilingual settings. Future studies should explore the long-term impacts of internet use on language acquisition and its potential integration with traditional teaching methods to create a more holistic and effective EFL learning environment.